The Effect of Price, Service Quality and Payment Method on Prospective Customers' Buying Interest â€œBathnbody_stuffâ€ - Mukhtarisa, Taqiyatul; Sitepu, Sri Nathasya Br (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Buying interest is a form of customer behavior that arises in response to objects that show the desire of potential customers to make purchases. This study aims to determine the effect of price, service quality and payment methods on the buying interest of potential customers Bathnbody_stuff. This research is a quantitative research. The population in this study is all Shopee customers who have an interest in buying online shopping through Shopee. The number of samples was determined using the Lameshow formula, which was 384 respondents. The primary data collection method was carried out by distributing questionnaires online using Likert scale measurements. The data analysis method uses multiple linear regression analysis with the help of SPSS 25 software. The results showed that prices and payment methods did not have a significant effect on buying interest. While the quality of service partially has a significant effect on the buying interest of potential customers.